Determination of emerging chlorinated byproducts of diazepam in drinking water. (March 2019) - Zhang, Xin; Yang, Yunjia; Zhang, Jing; Yang, Yi; Shen, Fan; Shen, Jianzhong; Shao, Bing
Abstract: Diazepam (DZP) is often found in source water and drinking water at dozens of nanograms per liter levels. The transformation of DZP in water chlorination disinfection process has aroused new concern because the toxic disinfection byproducts (DBPs) might be produced. However, the DBPs of DZP have not been fully identified, and their occurrence levels in drinking water have not been reported. In our chlorination experiment, five emerging DBPs of diazepam: (5-chloro-2-(methylamino) phenyl) (phenyl)methanone (BP-246), 6-chloro-1-methyl-4-phenylquinazolin-2(1H)-one (BP-271), N-(2-benzoyl-4, 6-dichlorophenyl)formamide (BP-294), methyl-(2-benzoyl-4-chlorophenyl) (methyl)carbamate (BP-304 (1)) and 6-chloro-4-methoxy-1-methyl-4-phenyl-1, 4-dihydro2H -benzo[ d ][1, 3]oxazin-2-one (BP-304 (2)), were tentatively identified by high-resolution mass spectrometry and further characterized by nuclear magnetic resonance spectroscopy. We developed a trace analytical method for the analysis of these five DBPs in drinking water based on solid-phase extraction (SPE) followed liquid chromatography coupled with electrospray ionization tandem mass spectrometric detection. Ultrahigh sensitivities were achieved with limits of detection as low as 7 pg per liter. The recoveries at different spiking levels were all higher than 80% except for that of BP-246. Four of the DBPs and DZP were detected in real drinking water samples at concentrations ranging from several to dozens of nanograms per liter with relatively high detection frequencies. This is the first report on the existence of DZP-DBPs in drinking water. The method and results will be useful for further studies on the occurrence, toxicity, human exposure and control measures of these DBPs. Graphical abstract: Image 1 Highlights: The emerging DBPs of diazepam were identified by mass spectrometry and NMR. A trace analytical method was developed for diazepam and it's DBPs in drinking water. Four DBPs were detected in drinking water samples collected in Beijing. This is the first report for the occurrence of diazepam DBPs in drinking water.